Interações entre Gnatocerus cornutus (Linnaeus, 1758) e Tenebrio molitor (Fabricius, 1798) (Coleoptera, Tenebrionidae) - Fischer, Marta Luciane; Wanto, Mônyka Maria; de Paula, Maria Cristina Zborowski (Agrarian, 2013)
The beetle Tenebrio molitor and Gnatocerus cornutus often co-inhabit in warehouses stored grain in tropical regions. Problems with human health associated with the use of synthetic pesticides, require new forms of control. Thus, there are questions about the asymmetry in the interactions between this species. The hypothesis is that the presence of G. cornutus limits the growth population of T. molitor. To check, there were 100 intra- and interspecific combinations between males and females with eggs, larvae and pupae. The adults and larvae preyed heterospecific eggs. Therefore, the co-existence of T. molitor and G. cornutus was mediated by symmetrical trophic relationships in which the species mutually control their populations.